The Secrets of Salantai Engraving Studio: Stanisław Czerski, the Mysterious Byks, and ‘The Wrong’ Plater - Braziūnienė, Alma (Knygotyra, 2024)
In the early 19th century, the short-living Salantai Engraving Studio became an exceptional phenomenon of the culture of Lithuania: it was here that engravings with Lithuanian (Samogitian) inscriptions were being made. Its founder Stanisław Czerski (1777–1833), who also worked there for a while, was denoted by a talented personality of broad interests. He was a talented philologist, a translator, pedagogue, engraver, ethnologist, a canon of the Samogitian Cathedral Chapter, and a Doctor of Theology. The article investigates the nature of the activity of Salantai Engraving Studio: whether the engravers using the fictitious name of Byks was related to it, if this could be Albert Gorski (1808–1860), the owner of Salantai Manor, with whom of the Plater family Stanisław Czerski was maintaining friendly relationships, as well as other debatable issues which, so far, have been presented in historiography in a multitude of different ways. The objective of this article is to specify some claims on Stanisław Czerski as a promoter of culture and Salantai Engraving Studio while challenging a number of misconceptions that previously were firmly established in historiography, while also providing novel insights in terms of explicating pseudonyms and other relevant issues. The sources of this research are publications in encyclopedias, reference publications and scholarly articles, while also touching upon the relevant archival sources in a number of memory institutions. This research employs content and source analysis methods along with the historical comparative method. The article raises a hypothesis that Salantai Studio was making not only copper engravings, but also publishing lithographs. Meanwhile, the Byks alias appears to have been used by two different engravers. The exact date of birth of Albert Gorski, the owner of Salantai Manor, and a disciple of Stanisław Czerski has been established. Archival sources were used to determine some facts of the biography of Albert Gorski, and his relationship with Stanisław Czerski has been outlined. The claim by Vaclovas Biržiška on the friendship between Stanisław Czerski and Jurgis Plateris (1810–1836) has been disproven. Hopefully, this article will serve for further more extensive research on Salantai Engraving Studio and its founder Stanisław Czerski.